O fluxo documental na Procuradoria da República no Estado do Pará (PR/PA) - FARIAS, Luis Fellipe Loureiro (2018)
The present work had as general objective to analyze the Management and Document Flow in the scope of the PR / PA, with a view to the organization and the appropriate technical treatment of the Archive, applying the documentary management and proposing to identify how the production and processing of these documents occurs and the documentary flow of the area in the Office of Federal Prosecution in the State of Pará, to verify the documentary treatment in the organ in question and it is necessary that there be a complete documentary management aiming at the diffusion and dissemination of the information, to avoid the unnecessary accumulation of documents and wrong deletion. The result of the research indicates that this theoretical / practical survey can contribute to the expansion and consolidation of this subject with the assistance of the professional Archivist.